Functionalized magnetic nanoparticles: Synthesis, characterization, catalytic application and assessment of toxicity - Neamtu, Mariana (Sci Rep, 2018)
Cost-effective water cleaning approaches using improved treatment technologies, for instance based on catalytic processes with high activity catalysts, are urgently needed. The aim of our study was to synthesize efficient Fenton-like photo-catalysts for rapid degradation of persistent organic micropollutants in aqueous medium. Iron-based nanomaterials were chemically synthesized through simple procedures by immobilization of either iron(II) oxalate (FeO) or iron(III) citrate (FeC) on magnetite (M) nanoparticles stabilized with polyethylene glycol (PEG). Various investigation techniques were performed in order to characterize the freshly prepared catalysts. By applying advanced oxidation processes, the effect of catalyst dosage, hydrogen peroxide concentration and UV-A light exposure were examined for Bisphenol A (BPA) conversion, at laboratory scale, in mild conditions. The obtained results revealed that BPA degradation was rapidly enhanced in the presence of low-concentration H(2)O(2), as well as under UV-A light, and is highly dependent on the surface characteristics of the catalyst. Complete photo-degradation of BPA was achieved over the M/PEG/FeO catalyst in less than 15 minutes. Based on the catalytic performance, a hierarchy of the tested catalysts was established: M/PEG/FeO > M/PEG/FeC > M/PEG. The results of cytotoxicity assay using MCF-7 cells indicated that the aqueous samples after treatment are less cytotoxic.